Constraints on the \(SU(3)_C SU(2)_L SU(3)_R U(1)_X\) Model from the Process \(W_2 → t b\) - Huong, Do Thi; Thao, Nguyen Huy (Communications in Physics, 2019)
We study the process \(pp → W_2 → t b\) in the \(SU(3)_C SU(2)_L SU(3)_R U(1)_X\) model. The production cross-section times branching ratio is determined. We use the LHC data to derive constraint on the new physical scale, \(m_W_2\), and the elements of right-handed quarks mixing matrix.